2017
DOI: 10.1016/j.jogn.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sibling Preparation Classes

Abstract: Objective To examine the effectiveness of sibling preparation classes to facilitate the adjustment of a firstborn child to the birth of a sibling. Design Longitudinal study with five measurement occasions: third trimester of the mother’s pregnancy and 1, 4, 8, and 12 months following the sibling’s birth. Setting Communities in southeastern Michigan. Participants Two hundred forty-one families, including mothers, fathers, and firstborn children. Methods Mothers and fathers completed questionnaires to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Bazı ebeveynler ilk doğan çocuğun olumsuz davranışları ile etkili bir şekilde başa çıkamadıkları için suçluluk ve üzüntü yaşayabilmektedirler. Ayrıca ebeveynler ilk çocuklarının küçük kardeşlerini kabul edip etmeyeceklerini ve iki çocuğun bakımını dengeleyip dengelemeyecekleri konusunda endişe duymaktadırlar (Beyers-Carlson & Volling, 2017). Naber ve arkadaşları (2018) tarafından yapılan bir meta analiz çalışmasında sağlık profesyonelleri tarafından düzenlenen kardeş hazırlık sınıflarına katılan çocukların doğumu olumlu, heyecan verici ve önemli bir yaşam olayı olarak değerlendirdiği ve ilk çocukların kardeşlerine karşı oluşturdukları endişe ve korkuların azaldığı bulunmuştur.…”
Section: Discussionunclassified
“…Bazı ebeveynler ilk doğan çocuğun olumsuz davranışları ile etkili bir şekilde başa çıkamadıkları için suçluluk ve üzüntü yaşayabilmektedirler. Ayrıca ebeveynler ilk çocuklarının küçük kardeşlerini kabul edip etmeyeceklerini ve iki çocuğun bakımını dengeleyip dengelemeyecekleri konusunda endişe duymaktadırlar (Beyers-Carlson & Volling, 2017). Naber ve arkadaşları (2018) tarafından yapılan bir meta analiz çalışmasında sağlık profesyonelleri tarafından düzenlenen kardeş hazırlık sınıflarına katılan çocukların doğumu olumlu, heyecan verici ve önemli bir yaşam olayı olarak değerlendirdiği ve ilk çocukların kardeşlerine karşı oluşturdukları endişe ve korkuların azaldığı bulunmuştur.…”
Section: Discussionunclassified
“…First, information was only collected from children's mothers, which may provide an incomplete perspective of their reactions. However, compared with the information provided by fathers and the children themselves, studies have revealed the high levels of accuracy and validity of mother-reported outcomes in a child's behaviors (Rescorla, 2005;Beyers-Carlson & Volling, 2017). Second, the study population was not a representative sample, which limits external validity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous research whereby birth children have reported that they did not feel they were equipped with enough information about the realities of fostering (Martin, 1993; Nordenfors, 2016; Poland and Groze, 1993; Pugh, 1996; Raineri, Calcaterra and Folgheraiter, 2018; Targowska, Cavazzi and Lund, 2016; Younes and Harp, 2007). When it comes to the outcomes of preparation, the literature on transition to siblinghood has identified mixed results, with some studies reporting positive effects on sibling rivalry (Fortier, et al., 1991) and recent research finding no benefit to family functioning (Beyers-Carlson and Volling, 2017) and highlighting how supportive co-parenting is more likely than preparation to help children adjust.…”
Section: Discussionmentioning
confidence: 99%